Are peatlands in different states with respect to their thermodynamic behaviour? A simple test of peatland energy and entropy budgets. Issue 12 (14th December 2021) - Worrall, Fred; Morrison, Ross; Evans, Chris; Kaduk, Joerg; Page, Susan; Cumming, Alex; Rayment, Mark; Kettridge, Nicholas
Abstract: Whilst all ecosystems must obey the second law of thermodynamics, these physical bounds and controls on ecosystem evolution and development are largely ignored across the ecohydrological literature. To unravel the importance of these underlying restraints on ecosystem form and function, and their power to inform our scientific understanding, we have calculated the entropy budget of a range of peat ecosystems. We hypothesize that less disturbed peatlands are 'near equilibrium' with respect to the second law of thermodynamics and thus respond to change by minimizing entropy production. This 'near equilibrium' state is best achieved by limiting evaporative losses. Alternatively, peatlands 'far‐from‐equilibrium' respond to a change in energy inputs by maximizing entropy production which is best achieved by increasing evapotranspiration. To test these alternatives this study examined the energy balance time series from seven peatlands across a disturbance gradient. We estimate the entropy budgets for each and determine how a change in net radiation (Δ R n ) was transferred to a change in latent heat flux (Δ λE ). The study showed that: (i) The transfer of net radiation to latent heat differed significantly between peatlands. One group transferred up to 64% of the change in net radiation to a change in latent heat flux, while the second transferred as little as 27%. (ii) Sites that transferred the most energy to latent heat flux were those that produced the greatest entropy. The study shows that an ecosystem could be 'near equilibrium' rather than 'far from equilibrium'. Abstract : We hypothesize that less disturbed peatlands have a different thermodynamic response in comparison to intact peatlands. We show this difference in how UK peatlands respond to changes in energy inputs. Disturbed, far‐from‐equilibrium peatlands respond to changes in net radiation by disproportionately increasing evaporation.